If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 = 5x + -4 + 7 Reorder the terms: 3 + 2x = 5x + -4 + 7 Reorder the terms: 3 + 2x = -4 + 7 + 5x Combine like terms: -4 + 7 = 3 3 + 2x = 3 + 5x Add '-3' to each side of the equation. 3 + -3 + 2x = 3 + -3 + 5x Combine like terms: 3 + -3 = 0 0 + 2x = 3 + -3 + 5x 2x = 3 + -3 + 5x Combine like terms: 3 + -3 = 0 2x = 0 + 5x 2x = 5x Solving 2x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2x + -5x = 5x + -5x Combine like terms: 2x + -5x = -3x -3x = 5x + -5x Combine like terms: 5x + -5x = 0 -3x = 0 Divide each side by '-3'. x = 0 Simplifying x = 0
| x^4+1500x^2+1250000=0 | | x*23=33 | | 7x=3x+26 | | 8x-(3x-6)=26 | | 7(2x-1)=11x+5 | | 2a+7=-2-3 | | H=68t-8t | | (9(y+5)-18)+(3(y-3)+5)= | | 5=7-7x | | p^2+4p+4=40 | | 2x-(x+1)= | | (8y-5)6y-7= | | 4(x+5)5=2x-4 | | 6d-11/2=2d-13/2 | | (X+10)2=y+100 | | 24x+19x=180 | | 7/10x=14/5 | | 17-x=172 | | 70-61x+4x^2=0 | | -3=-6-x | | -24+5x+x^2=0 | | x^3+3x^2-15x=0 | | -24+x^2=0 | | -9(x+9)+4=-77 | | 18000=p(1+.12*2) | | 21y=4(5x-6) | | 7(4s+1)=63 | | 70-16x+4x^2=0 | | 2b=20-28 | | 5c+15=15+4c-2 | | 5+x-4=14 | | 7x+4-2x=5x+4 |